Leadership at the helm: Essential skills and knowledge for effective management in Islamic Economics and Finance schools - Ibrahim, Mohamed Abdeltawab; Abdullah, Arnida; Ismail, Ismi Arif; Asimiran, Soaib (Elsevier, 2024)
A skilled principal is an invaluable asset in the evolving landscape of higher education institutions, where challenges continually arise and the global economy demands adaptability. This study explored the essential skills and knowledge necessary for principal roles in Islamic Economics and Finance (IEF) schools. A qualitative multiple-case study approach was employed, and semi-structured interviews were conducted with 34 academics from four IEF schools at public universities in Saudi Arabia and Malaysia. The study revealed six essential skill and knowledge areas that IEF school principals must possess to thrive: advocacy for IEF education, developing and communicating a clear strategic vision, efficiently managing resources and workloads, fostering a collegial environment, providing effective instructional leadership, and building and sustaining strong partnerships. Improving the skills and knowledge of IEF principals can lead to better school management and education. The findings of this study hold significant importance in the advancement of leadership programs designed for IEF school principals and provide valuable insights for policymakers and stakeholders regarding the indispensable knowledge and skills that principals of IEF schools must possess. © 2024